Why Has the U.S. Economy Become Less Correlated with the Rest of the World? - Heathcote, Jonathan; Perri, Fabrizio (American Economic Review, 2003)
In this paper we do two things. First we document that over the last 40 years the U.S. business cycle has become less synchronized with the cycle in the rest of the world. Second we try to explain why this has happened. We use a general-equilibrium model as a tool to discriminate between two alternative explanations: (i) a change in the nature of real shocks, and (ii) an increase in U.S. financial integration with the rest of the world. Our results indicate that financial integration has played the major role in producing the observed changes in international co-movement.